DISPARITAS PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA NARKOTIKA - Devy Iryanthy Hasibuan; Syafruddin Kalo; Suhaidi Suhaidi; Madiasar Ablisar (Universitas Sumatera Utara, 2015)
ABSTRACT Conditions of punishment against the perpetrators of the crime of narcotics in general practice caused the disparity in the imposition of criminal punishment against narcotics. some narcotics criminal cases that have been Composed by a criminal court judge, a criminal cause disparities among different judges in deciding cases against the same. In addition to disparities that occur in sentences by fellow judges, the disparity also occurs between the the imposition of criminal prosecution. Concluded, first, punishment against perpetrators of narcotics under Law No. 35 of 2009 on Narcotics in the court ruling could potentially lead to disparities in the criminal because the interval between the minimum criminal penalty provisions and open wide maximum criminal. Second, the factors that cause the disparity in the criminal narcotic crime, among others, is no operation of the SPP elements as appropriate, differences in philosophy espoused by each judge is different, the absence of sentencing guidelines for judges in imposing a criminal, an independent judiciary, and uncontrolled disparities in the criminal cases narcotic crime can be done in the most effective way is to establish a sentencing guidelines. Keywords : Disparities Punishment, Narcotics, and Sentencing Guideliner